Problems facing educational services in the main cities of Muthanna Province - Jabbar Mohsen, Lect .Dr. Waleed (Basra studies journal, 2025)
The research aims to address some of the problems facing educational services in the cities (Samawa, Al-Rumaitha, Al-Khader) and finding appropriate solutions. It is seen that (32.1%, 43.4%, and 35.5%), respectively, of the schools in Al-Samawa, Al-Rumaitha, and Al-Khidr need renovation Also the problems related to the school administrations and the teaching staff, range (84.9%, 78.6%, 66%), respectively, from the administrations of the cities (Samawah , Al-Rumaitha, Al-Khidr) that faces some problems and difficulties in their work. While (79.4%, 67.9%, 70.2%) respectively of the teaching staff in the cities (Samawah, Al-Rumaitha, Al-Khidr) they face a difficulties in their works, in addition to many problems of students, like students failing and leaving of their study. As the percentage of students who failed in their studies was (17.9%, 14.1%, 20%) respectively in the cities (Samawa, Al-Rumaitha, Al-Khidr) and the body of students who dropped out during the academic year (2019-2020) in the cities (Samawa, Al-Rumaitha, Al-Khidr) was about (2.5%, 1.3%, 2.2%), respectively of the total number of students and students, aged They were recruited (75361, 32770, 17132) students in the three cities, respectively, during the same academic year. The research also included set of results, most notable one was the failure in complete in the school buildings that were referred for investment on time. The most important proposals are to work on completing the construction of lagging school buildings in order to Reducing double shifts in schools.